2013
DOI: 10.1136/bmjopen-2013-002893
|View full text |Cite
|
Sign up to set email alerts
|

How active are our children? Findings from the Millennium Cohort Study

Abstract: ObjectiveTo describe levels of physical activity, sedentary time and adherence to Chief Medical Officers (CMO) physical activity guidelines among primary school-aged children across the UK using objective accelerometer-based measurements.DesignNationally representative prospective cohort study.SettingChildren born across the UK, between 2000 and 2002.Participants6497 7-year-old to 8-year-old singleton children for whom reliable accelerometer data were available for at least 10 h a day for at least 2 days.Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
182
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(203 citation statements)
references
References 41 publications
10
182
4
3
Order By: Relevance
“…Recent evidence now indicates that a large proportion of children and adolescents routinely fail to accumulate recommended physical activity guidelines proposed by leading health authorities ( 36,42 ). Of particular concern, researchers have shown that physical activity levels appear to peak at approximately 6 years of age, after which there is a consistent decline into adolescence and adulthood ( 126).…”
Section: Problem 1: Physical Inactivitymentioning
confidence: 99%
“…Recent evidence now indicates that a large proportion of children and adolescents routinely fail to accumulate recommended physical activity guidelines proposed by leading health authorities ( 36,42 ). Of particular concern, researchers have shown that physical activity levels appear to peak at approximately 6 years of age, after which there is a consistent decline into adolescence and adulthood ( 126).…”
Section: Problem 1: Physical Inactivitymentioning
confidence: 99%
“…Children of primary school age in the United Kingdom (UK) engage in sedentary behaviour ((low energy expenditure activities) in a seated or reclined position during waking hours (Sedentary Behaviour Research Network, 2012)) for between 5-7 hours per day (Griffiths et al, 2013). In addition, levels of participation in moderateto-vigorous physical activity are low (Griffiths et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, levels of participation in moderateto-vigorous physical activity are low (Griffiths et al, 2013). Schools are frequently used as contexts for promoting children's health due to the ability to maximise reach, availability of existing resources, and possibility of curricular integration and sustainability (Fairclough et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This grade was influenced by the quality of data available to inform this indicator. Specifically, the MCS 7,8 provided the highest quality data (in terms of sample size, sampling strategy, and objective measures of PA employed) though data were only available for 7 to 8 year old children. As the grade for this indicator should reflect children of all ages, data from the HSE (2008) 4 and the HBSC (2010) 9 were included.…”
Section: Resultsmentioning
confidence: 99%